Becoming the Metalinguistic Mind: The Development of Metalinguistic Abilities in Children from 5 to 7 - Sergio Melogno; Maria Antonietta Pinto; Marco Lauriola (Children, 2022)
The object of this study is the development of metalinguistic abilities in an age range—5 to 7 years—where an important turn takes place in education, namely the transition between kindergarten and primary school. Based on the literature starting from the 70’s of the last century, embryonic forms of awareness of how language variation can be manipulated to convey variation in meaning are widely attested in preschoolers. These forms, however, denote an intuitive and implicit level of awareness and will attain a “meta-level”, based on more systematic and explicit reflectiveness, later in development in correlation with cognitive, linguistic, and educational factors. To measure the development of these abilities across the above age range, we recruited 160 native Italian-speaking children from 5 to 7, with comparable numerosity at each age, gender balance, average socio-cultural background, and no cognitive nor neuropsychological impairment. We used 6 metalinguistic tasks, the Raven’s CPM, a lexical and grammatical ability tests. The results showed a significant increase in all the measures across the span considered and correlations between all the measures. A factor analysis on the metalinguistic tasks showed that a single factor accounted for a large part of the common variance.